The Role of Product Display and Store Layout in Shaping Consumer Loyalty Through Shopping Experience at M2S Speed Shop - Ronda Deli Sianturi; Dinda Maysaroh Harahap; M.Mirza Fikhar; Irwangunawan; Aulia Syahputri (Jurnal Price : Ekonomi dan Akuntasi, 2026)
This study aims to analyze the influence of product displays and store layout on consumer loyalty through the mediation of shopping experience in the context of the M2S Speed ​​Shop automotive retailer. This study used a qualitative approach with a phenomenological design focused on an in-depth understanding of consumers' experiences interacting with the physical store environment (servicescape). Data were obtained through participant and non-participatory observation, visual documentation, and consumer behavior analysis, including movement patterns, product interactions, and levels of consumer engagement in the store. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña through an iterative process of data condensation, data presentation, and conclusion drawing, based on servicescape and retail experience theories. The results indicate that product displays act as a cognitive structuring mechanism that enhances ease of information processing (cognitive fluency), while store layout functions as a spatial navigation system that influences consumer exploration patterns within the store. These two elements do not directly influence consumer loyalty, but rather through the mediation of the shopping experience, which encompasses cognitive, emotional, sensory, and behavioral dimensions. Shopping experience has been proven to be a key variable in shaping consumer loyalty, as reflected in increased repeat purchase intention, store trust, and positive word-of-mouth.